ROUTING MISBEHAVIOR IN MOBILE AD HOC NETWORKS - ALSOUFI , DELAN SHERZAD; ALI , ISMAIL AMIN (Journal of Duhok University, 2023)
An ad hoc network is a temporary network that consists of wireless mobile hosts. Due to the absence of a centralized or structured infrastructure, a host may need assistance in forwarding a packet to a desired location. This is applicable in the cases whereby a limited range of transmissions is visible in mobile hosts. Dynamic Source Routing (DSR) is a simple but effective protocol intended specifically for those networks that lack a predetermined infrastructure. However, DSR becomes less reliable and may show misbehavior when network topology changes rapidly. One such misbehavior occurs when some ‘selfish’ nodes contributing in route discovery and safeguarding of the network refuse to send data packets. To address this problem and improve the throughput of MANETs, this paper proposes a modified DSR protocol based on two techniques: a 2ACK scheme and a pathrater extension. This paper has outlined the newly proposed and improved method in the attempt of enhancing the DSR protocol